Chrononutrition, Social Support, and Sleep Quality Associated with Overweight Among Health Students - Agus Maulana; Fajria Saliha Puspita Prameswari; Isti Kumalasari; Widya Astuti (PT Ilmu Data Indonesia, 2026)
Background: Obesity and overweight are major risk factors for morbidity and mortality from non-communicable diseases, and health students are particularly vulnerable due to demanding academic schedules and high study loads. In Indonesia, the prevalence of overweight and obesity among medical students reached 35.5% in 2023, reflecting a concerning level that warrants further investigation. Purpose: This study aimed to examine the association between chrononutrition, social support, sleep quality, and energy and protein intake with the occurrence of overweight among health students, and to identify the most dominant factor influencing this condition. Methods: This quantitative analytic study used a cross-sectional design involving 90 health students at Universitas Pendidikan Indonesia, selected through proportionate stratified random sampling based on inclusion criteria. Data were collected using the Chrononutrition Profile Questionnaire (CPQ), the Social Support for Eating Habits (SSEH) questionnaire, the Pittsburgh Sleep Quality Index (PSQI), a 2 x 24-hour food recall, and anthropometric measurements. Data were analyzed using chi-square tests and multiple logistic regression. Results: Overall, 47.80% of students were classified as overweight. Eating window (OR = 0.34), family support (OR = 2.69), and sleep quality (OR = 3.24) were significantly associated with overweight. Multivariate analysis identified family support as the most dominant factor influencing overweight among students. Conclusion: Family-based interventions are essential in preventing overweight among health students by promoting healthy eating patterns, appropriate chrononutrition behaviors, and good sleep quality, alongside consistent motivation and supervision to support sustained healthy lifestyle behaviors.